Transmission Network Cost Allocation Considering Counterflows - Arias-Albornoz, M (2011)
This paper presents a methodology for allocation of fixed costs of transmission based on the Y-modified and the electrical circuit theory. The use of the transmission network is determined from the contribution of each generator and load to the power flow in lines. The allocation process is carried out considering counterflows and distinguishing between the used and reserve capacity of the lines. According to the results, the methodology proved to be adequate, since it ensures complete recovery of transmission costs and provides financial incentives to agents who contribute to the security and reliability of the system and to the postponement of investment in transmission as well. © 2011 IEEE.